1980
DOI: 10.1079/bjn19800098
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in plasma retinol-binding holoprotein concentration in japanese quail (Conturnix coturnix japonica)

Abstract: I. Seasonal changes in retinol-binding holoprotein (holoRBP) concentration in plasma of groups of male and female Japanese quail (Coturnir corurnix juponicu) were examined over 18 months. 2.In Expts I and z the birds were maintained under natural lighting conditions and in Expt 3 under artificial-light photoperiods corresponding to the changing daylength at 56" N latitude. All groups were at 18-20" and received Superlayers' (Rank Hovis McDougall) pellet diet.3. The mean plasma holoRBP concentration in all grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1980
1980
1984
1984

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…Similarly, the onset of egg laying and cloacal gland development were also delayed by the equivalent of 2 months of solar-dial clock time. The mean maximum mid-summer levels of holoRBP were lower than those observed in birds on the annual cycle (Heaf & Glover, 1979;Glover et al 1980) and in males the expected peak in mid-summer was reduced to a level which was only just significant. Nevertheless, the changes in RBP and TBPA over the cycle were sufficient to produce a marked effect on the ratio of the two proteins as illustrated in Fig.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Similarly, the onset of egg laying and cloacal gland development were also delayed by the equivalent of 2 months of solar-dial clock time. The mean maximum mid-summer levels of holoRBP were lower than those observed in birds on the annual cycle (Heaf & Glover, 1979;Glover et al 1980) and in males the expected peak in mid-summer was reduced to a level which was only just significant. Nevertheless, the changes in RBP and TBPA over the cycle were sufficient to produce a marked effect on the ratio of the two proteins as illustrated in Fig.…”
Section: Discussioncontrasting
confidence: 49%
“…In this connection, it was interesting to note that in Japanese quail, where the variations in TBPA and holoRBP were studied over 1 -5 annual cycles (El-Sayed et al 1980;Glover et al 1980), that egg laying commenced in late February in the first cycle whereas in the second cycle it did not occur until late March. Both these events followed the times which the molar ratio of TBPA : RBP changed to 1-0 by approximately the same delay of 10-12 days in each cycle, indicating a closer link between gonadal development (for egg laying) and TBPA : holoRBP ratio than between a particular photoperiod alone.…”
Section: Tbpa and Retinolmentioning
confidence: 98%
See 1 more Smart Citation
“…In domestic fowl, reproduction continues normally up to the point of egg-laying but the embryo fails to develop beyond day 2 unless vitamin A derivatives, of which the most potent is retinol, are injected into the eggs before incubation (Thompson, Howell, Pitt & McLaughlin, 1969). More recently it has been shown that the concentration of plasma retinol-binding holoprotein (holoRBP, protein with retinol bound) undergoes a seasonal increase in autumn in sheep (Glover, Jay, Kershaw & Reilly, 1976) and in spring in Japanese quail (Coturnix coturnix japónica; Glover & Large, 1977;Glover, Large & Heaf, 1980). In both species a two-to threefold rise in plasma holoRBP concentration has been observed at the beginning ofthe sexually active part of the annual cycle of gonadal growth and regression, followed by a steep fall about 2 months later.…”
Section: Introductionmentioning
confidence: 98%
“…Plasma RBP levels, and therefore retlnol concentrations, are known to increase with increased levels of steroid sex-hormones as found In the natural cycles of females of several species. Including humans (22)(23)(24)(25)(26). This mechanism Is proposed to operate through Increased hepatic synthesis of RBP and subsequent mobilization (26).…”
Section: Univas^mentioning
confidence: 99%